Distribution of the big-headed turtle Platysternon megacephalum Gray, 1831 in Thailand and a case study on population status and conservation management at Chiang Dao Wildlife Sanctuary, Chiang Mai Province - Kruewan Pipatsawasdikul (Chulalongkorn University, 2012)
Thesis (Ph.D.)--Chulalongkorn University, 2009